Severe coagulation factor VII deficiency caused by a novel homozygous mutation (p. Trp284Gly) in loop 140s. Issue 4 (June 2016) - Hao, Xiuping; Cheng, XiaoLi; Ye, Jiajia; Wang, Yingyu; Yang, LiHong; Wang, Mingshan; Jin, Yanhui
Abstract : Congenital coagulation factor VII (FVII) deficiency is a rare disorder caused by mutation in F7 gene. Herein, we reported a patient who had unexplained hematuria and vertigo with consanguineous parents. He has been diagnosed as having FVII deficiency based on the results of reduced FVII activity (2.0%) and antigen (12.8%). The thrombin generation tests verified that the proband has obstacles in producing thrombin. Direct sequencing analysis revealed a novel homozygous missense mutation p.Trp284Gly. Also noteworthy is the fact that the mutational residue belongs to structurally conserved loop 140s, which majorly undergo rearrangement after FVII activation. Model analysis indicated that the substitution disrupts these native hydrophobic interactions, which are of great importance to the conformation in the activation domain of FVIIa.